Karman and Compassion: Animals in the Jain Universal History - De Clercq, Eva (Religions of South Asia, 2013)
As a religious tradition which largely defines itself by its propagation of non-violence (ahimsa) and respect for all living beings, Jainism gives particular attention to the wellbeing of animals, for example, in the prescription of a strict (lacto-)vegetarian diet, in advocating animal rights and the sponsorship of animal shelters. Against this background, this article examines the presence of animals and other non-human beings in Jaina mythology, more precisely the so-called Jaina Universal History. This Universal History in practice consists of the biographies (caritra or purana) of 63 heroes (salaka- or maha-purusas), many of whom have parallels in broader South Asian epic, puranic or narrative traditions. This article introduces the various ways animals are dealt with in these Jaina puranic narratives, and will focus in particular on their symbolic value as representatives of human heroes.